Analysis of the kinase-related protein gene found at human chromosome 3q21 in a multi-gene cluster: Organization, expression, alternative splicing, and polymorphic marker - Watterson, D. Martin; Schavocky, James P.; Guo, Ling; Weiss, Curtis; Chlenski, Alexandre; Shirinsky, Vladimir P.; Van Eldik, Linda J.; Haiech, Jacques (Journal of cellular biochemistry, 1999)
We report the amino acid sequence, genomic organization, tissue expression, and alternative splice patterns for the human kinase related protein (KRP) gene, as well as the discovery of a new CA repeat sequence polymorphic marker in an upstream intron of the myosin light chain kinase (MLCK) gene. The KRP/MLCK genetic locus is a prototype for a recently discovered paradigm in which an independently regulated gene for a non‐enzymic protein is embedded within a larger gene for a signal transduction enzyme, and both classes of proteins are involved in the regulation of the same cellular structure. The MLCK/KRP gene cluster has been found only in higher vertebrates and is localized to human chromosome 3q21. The determination of the human KRP amino acid sequence through cDNA sequence analysis and its comparison to the exon/intron organization of the human KRP gene revealed an alternative splice pattern at the start of KRP exon 2, resulting in the insertion of a single glutamic acid in the middle of the protein. Examination of tissue distribution using Northern blot analysis revealed that the human expression pattern is more similar to the well‐characterized chicken KRP gene expression pattern than to rodent or rabbit. Unexpected differences of the human gene from other species is the apparent expression of the human gene products in adult cardiac muscle, an observation that was pursued further by the production of a site‐directed antiserum and immunohistochemistry analysis. The results reported here provide insight into the conserved and variable features of this late evolving genetic paradigm, raise new questions about the molecular aspects of cardiac muscle regulation, and provide tools needed for future clinical studies. The comparative analysis of the MLCK/KRP locus, combined with the recent discovery of a similar genomic relationship among other signal transduction proteins, suggest a diverse distribution of this theme among signal transduction systems in higher vertebrate genomes and indicate the utility of comparative genomics in revealing late evolving genetic paradigms. J. Cell. Biochem. 75:481–491, 1999. © 1999 Wiley‐Liss, Inc.